Analisis Pemahaman Matematis Siswa Kelas V SDN 39 Mata Air Barat Padang - Jon Hendri; Nanang Kosim; Reni Manovtri; Enni Gustina Yaste; Trinda Farhan Satria (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This research is motivated by understanding of mathematical conceptsstill low in class V SDN 39 Mata Air Barat. This is caused bylearning that is carried out is less interesting and understanding of mathematical conceptslow students. This study aims to find out analyzeunderstanding of mathematical concepts for class V SDN 39 Mata Air Barat Padang.This type of research is a type of quantitative descriptive research. Populationin this study were all students of class V SDN 39 Mata Air Barat. The sampling technique was carried out by means of purposive sampling, selected class V as the class being analyzed. The research instrument is in the form ofposttest by using an indicator of understanding the concept that functions formeasure the level of understanding of students' mathematical concepts. The average score of students' understanding of mathematical concepts in the sample classis 96 with a maximum value of 100 and a minimum value of 88 and a standard deviation3,7